Variability study of entomopathogenic nematode populations (Heterorhabditidae) from Argentina - Achinelly, Maria Fernanda (2016)
Entomopathogenic nematodes (EPN) belonging to the Heterorhabditidae family are lethal parasites of soil-dwelling insects. Two species were reported in Argentina: Heterorhabditis argentinensis and Heterorhabditis bacteriophora characterized mainly by morphometric features. In this work a comparative and phylogenetic study between five Heterorhabditis populations from Argentina was conducted to analyze the variability between strains and to evaluate the taxonomic position of Heterorhabditis argentinensis. The PCA analyses of morphometric characters separated the larger juvenile, female and male H. argentinensis from H. bacteriophora populations. The juvenile (IJs) stage provided the clearest separation of Heterorhabditis populations presenting the least variability between strains. The variable L and MBW were highly related to H. argentinensis IJs. Three groups were separated by this stage considering PC1 and PC2: one formed by H. bacteriophora OLI, RIV and RN strains, (isolates from Córdoba and Río Negro province), one for H. bacteriophora VELI strain (Buenos Aires province) and one for H. argentinensis (Santa Fe province). Heterorhabditis bacteriophora VELI and H. argentinensis isolated from regions with more rainfalls and humidity presented larger values for morphometric features. Molecular analyses showed the Argentinian populations (H. bacteriophora VELI strain and H. argentinensis), forming a same clade, with six other H. bacteriophora populations (not from Argentina) with a genetic similarity between them of 99%. Heterorhabditis argentinensis presented one unique nucleotide that was not present in any of the other species of the clade. Considering the results of this study H. argentinensis would be conspecific to H. bacteriophora, constituting a strain with a great morphometric variation where the host and climatic conditions could have influenced on the measurements.